Quantifying the long-term recovery of the protective effect of forests against rockfall after stand-replacing disturbances - May, Dominik; Moos, Christine; Dorren, Luuk; Noyer, Estelle; Temperli, Christian; Schwarz, Massimiliano (Frontiers in Forests and Global Change, 2023)
Introduction Increasing disturbances may significantly impact the long-term protective effect of forests against natural hazards. Quantifying the temporal development of the protective effect of forests is thus crucial for finding optimal management strategies. Methods In this study, we analyzed the long-term recovery of the protective effect of the secondary stands of spruce (Picea abies), fir (Abies alba), and beech (Fagus sylvatica) forests against rockfall after stand-replacing disturbances based on data of the Swiss National Forest Inventory (NFI). We therefore derived the age of the inventoried forest stands of those tree species based on a growth parametrization and quantified their energy dissipation capacity in rockfall processes as a function of stand age. We then analyzed the development of their protective factor for varying rockfall dispositions. Results Generally, it takes between 50 and 200 years to regain the maximum possible protective effect, depending from the site conditions and the rockfall disposition. This implies that the recovery of the protective effect after a severe disturbance may require more time than the decay of the protective effect from disturbance legacies, resulting in a long lasting gap of the provided protection. Discussion The here presented approach can serve as a basis to estimate the general range of recovery of the protective effect of beech, fir and spruce forests against rockfall provided by forest stands. Future research should analyse the effects of environmental and forest conditions as well as varying disturbance intensities and legacies to enable the assessment of specific trajectories of the short- and long-term recovery of the protective effect.